2020
DOI: 10.1007/s11705-020-1992-z
|View full text |Cite
|
Sign up to set email alerts
|

CO2 capture using membrane contactors: a systematic literature review

Abstract: With fossil fuel being the major source of energy, CO2 emission levels need to be reduced to a minimal amount namely from anthropogenic sources. Energy consumption is expected to rise by 48% in the next 30 years, and global warming is becoming an alarming issue which needs to be addressed on a thorough technical basis. Nonetheless, exploring CO2 capture using membrane contactor technology has shown great potential to be applied and utilised by industry to deal with post- and pre-combustion of CO2. A systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 524 publications
2
14
0
1
Order By: Relevance
“…Some potential emerging topics related to main keywords such as “HFM”, “hollow fibers”, “gas separation”, “water treatment”, “membrane contactor”, “membrane fouling” and “MBR” have been listed in Table 4 . The contents of Table 4 demonstrate that the most recent and emerging trends in HFM research areas from the present work are in accordance with the research trends reported in various HFM-related literature reviews by various authors [ 5 , 59 , 60 , 61 ].…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Some potential emerging topics related to main keywords such as “HFM”, “hollow fibers”, “gas separation”, “water treatment”, “membrane contactor”, “membrane fouling” and “MBR” have been listed in Table 4 . The contents of Table 4 demonstrate that the most recent and emerging trends in HFM research areas from the present work are in accordance with the research trends reported in various HFM-related literature reviews by various authors [ 5 , 59 , 60 , 61 ].…”
Section: Resultssupporting
confidence: 88%
“…Some potential emerging topics related to main keywords such as "HFM", "hollow fibers", "gas separation", "water treatment", "membrane contactor", "membrane fouling" and "MBR" have been listed in Table 4. The contents of Table 4 demonstrate that the most recent and emerging trends in HFM research areas from the present work are in accordance with the research trends reported in various HFM-related literature reviews by various authors [5,[59][60][61]. The membrane types and processes that appeared most frequently in recent years include mixed matrix membranes, ceramic membranes, sweeping gas membranes, membrane distillation, forward osmosis, DCMD, photocatalytic degradation, pressure retarded osmosis, hydrophobic modification, dual-layer HFM, superhydrophobic, zeolite membranes, nickel membranes and air gap distillation.…”
Section: Research Hotspots and Future Trendssupporting
confidence: 88%
“…There are several familiar approaches to reduce CO 2 content in the atmosphere, such as adsorption, absorption, cryonic, and using a membrane (Hafeez et al 2020 Since some absorbents have chemical reactions with CO 2 , a chemical process is consequently required in the desorption step, causing a large sum of absorbents to be wasted. Further, chemical solvents seriously damage facilities due to the corrosion phenomenon, raising the operational costs (Ji et al 2018; Wang et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Membrane contactors also have some disadvantages, where they can be minimized by using an ideal membrane with high porosity and well defined pore size together with short mass transfer paths [7]. Hafeez et al [9], reviewed the usage of membrane contactors as a capture system and showed that not only membrane contactors are widely used but also amine solvents for CO 2 removal. Constantinou et al [10][11][12][13], studied the CO 2 absorption in a silicon nitrite mesh contactor, in a flat membrane micro-structured contactor and in a metal mesh micro-structured reactor using diethanolamine (DEA), monoethanolamine (MEA) and sodium hydroxide (NaOH) solutions.…”
Section: Introductionmentioning
confidence: 99%